Legal Hermeneutics as a Method 0f Rechtsvinding In Judicial Practice - Vantriano Oktavian Garat; Gamal Abdul Nasil; Rijal Ibnu Sani; Aris Gumilar (Universitas Muhammadiyah Tangerang, 2024)
Legal certainty and justice constitute fundamental objectives of law enforcement. However, statutory provisions are often incomplete and unable to fully anticipate concrete legal events. In such circumstances, judges are required to engage in legal discovery (rechtsvinding). This study examines legal hermeneutics as a philosophical and methodological foundation for legal interpretation in judicial practice. Using normative legal research with a conceptual approach, this article argues that legal hermeneutics enables judges to bridge the gap between legal texts and social realities through a dialogical process between text, context, and contextualization. The hermeneutic circle, fusion of horizons, and pre-understanding play central roles in shaping judicial reasoning. The case of Marbury v. Madison (1803) demonstrates how hermeneutic reasoning contributes to creative legal development. Legal hermeneutics thus provides an alternative paradigm beyond strict legal positivism, enabling a balanced realization of legal certainty, utility, and justice.